Efektivitas Metode Team Games Tournament (TGT) Terhadap Hasil Belajar Akidah Akhlak Siswa Kelas 6 MDTA Dzuhainah Kota Tasikmalaya - Nailatunnajah, Nada; Sintiana Nur Ilah, Sinta; Mahfira Maulani, Haniifan; Rahmawati, Rima; Nurpadilah, Maila; Sulistiani, Mirna; Oktiwanti, Lesi (Universitas Muhammadiyah Magelang, 2026)
The low motivation and learning outcomes of students in non-formal religious educational institutions are problems that have not been widely addressed through innovative learning methods. This study aims to test the effectiveness of the Team Games Tournament (TGT) method in improving the learning outcomes of Akidah Akhlak (Islamic Aqidah) of 6th grade students at Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) Dzuhainah, Tasikmalaya City. The study used a quantitative approach with a one-group pretest-posttest design on 22 students. The learning model was validated by three validators using the Aiken's V index before implementation. Learning outcome data were analyzed using the Wilcoxon Signed-Rank test. The model validation results showed an average Aiken's V index of 0.913 (high category). After implementing TGT in one 90-minute session, the average student score increased from 61.82 to 78.41 with an average gain of 16.59 points (an increase of 26.84%). The Wilcoxon test yielded a Z value of -4.107, greater than the critical value of 1.96 (α = 0.05), thus the improvement was declared statistically significant. All 22 students (100%) experienced an increase in their scores. 82% of students achieved scores above the KKM of 70. The TGT method demonstrated significant effectiveness in improving cognitive learning outcomes in the context of a single-session implementation at MDTA Dzuhainah, although the generalization of the findings requires further validation through a more robust research design.